Familial Breast Cancer in Costa Rica: An Initial Approach - Ramírez Monge, Adriana (2004)
Cancer is a worldwide problem because of its high rates of incidence and associated mortality. By 2000, more than 6.2 million people died from this illness worldwide. Among all types of cancer, breast cancer is one of the most studied. Each year, one million new cases are diagnosed around the world. We can classify breast cancer into two main kinds: sporadic cases and those which are a product of inherited genetic alterations. Approximately 5-10% of breast cancer cases are the result of inherited mutations, or alterations in breast cancer susceptibility genes, BRCA1 and BRCA2. Like other countries, Costa Rica possesses high rates of incidence and mortality for breast cancer. According to the “Registro Nacional de Tumores” (National Office of Tumor Records), in 2000 breast cancer had the highest rate of incidence and in 2002 it had the highest rate of mortality in comparison to other types of cancer. For this reason and the generalized lack of knowledge in the field we conducted an epidemiological research on breast cancer patients from Hospital San Juan de Dios, San José, Costa Rica, to find families with a history of breast cancer, and to determine the occurrence of familial cases within the population studied. So far, we have found 23 families, within which we discovered very informative cases that have rendered the identification of a pattern of inheritance. These findings allow us to announce that in Costa Rica there are several cases of inherited breast cancer and that we need more research is needed to improve the prevention, control, and treatment of this disease.